(untitled) (Revista Rupturas, 2017)
This article addresses on the clientelist relations between the Costa Rican State and the Central Azucarera del Tempisque, S.A. (CATSA), in a period between 1975 and 1990. CATSA was a company forged with public funds, which benefited the Guanacastecan sugarcane sector and then, in a convulsive context, was transferred to private investors. In its early years, the mill was plagued by multiple crises, such as a labor strike and financial problems that bordered it to bankruptcy. This allowed the weakening of the Wellfare state and favoring the promulgation of free market theories. The methodology used, related to business history, analyzed the origins of the company, its leaders and main troubles in the years under the state control.